Karakteristik dan Patogenisitas Streptococcus Agalactiae Tipe ?-hemolitik dan Non-hemolitik pada Ikan Nila - Handayani Hardi, Esti; -, Sukenda; Harris, Enang; Mariana Lusiastuti, Angela (Jurnal Veteriner; Vol 12, No 2 (2011), 2012)
Streptococcus agalactiae was isolated from cultured Nile tilapia (Oreochromis niloticus) in Cirata gulfand Klaten. The isolates were Gram positive cocci, oxidative fermentative positive, motility, and catalasenegative, grown on media containing NaCl 6.5%, ?-haemolytic and non-haemolytic. Two types of S. agalactiae(?-haemolytic and non-haemolytic) are different from their variety of sugars fermentation. Strains ?-haemolytic can ferment more sugars, including arabinose, sorbitol, lactose, and trehalose. Experimentalinfectivity trials on Nile tilapia (size 15 g), non-haemolytic type showed more virulent. This type causedfaster mortality, more severe behavior changes, and pathology changes than â-haemolytic type. NonhemoliticS. agalactiae caused 48% mortality 6-24 hours after injection, whereas â-haemolitic type caused17% mortality which it occured in 48 hours after injection (mortality of fish control 2,22%). Behaviordisease signs caused by non-haemolitic S. agalactiae started to happen 6 hours after injection whereas 12hours in ?-haemolytic type infection. Histopatological changes were observed on fish eye, spleen, andbrain. Hyperaemia, hyperthrophi, degeneration, and necrosis were also found on infected fish. Thisresearch was concluded that non-haemolytic of S. agalactiae was more virulent than ?-haemolytic.
Keywords: Characterization, pathogenicity, Streptococcus agalactiae, Oreochromis niloticus